Analisis Wacana Kritis Norman Fairclough dalam Media Sosial: Peringatan Karbala (Arbain) di Media Sosial - Ika Firdawati Sanger (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Social Media is a place to access information quickly, so social media is often used on minority religious issues in Indonesia, but the problem now is how the media plays a role in shaping minority religious discourse (Shia ) in the implementation of arbain 2023 ( the day of the Shahada of Sayyidina Husain bin Ali), social media (Youtube) spread the commemoration of Karbala day with messages that controversy with the text of the Karbala commemoration is a threat to the continuity of the majority religion (Sunni). This paper is focused on how the media builds power in the text displayed regarding minorities and majorities. The purpose of this paper will discuss, first, how the concept of Critical Discourse Analysis. Second. How to form a critical discourse analysis . Third, How to analyze critical discourse in YouTube content (Ashura/Arbain warning). The method in this writing uses the method of library research (Reseach Library). The importance of critical discourse analysis in this study in order to contribute readers to be wiser in studying the information spread in social media, in order to be able to consider how the information disseminated and obtained is not a reference in behaving and behaving towards others.